The Spirituality of Rural Muslim Communities through Jam’iyyah Nahdlatul Ulama Routine Activities - Hendri Hermawan Adinugraha; Maaz Ud Din; Ali Muhtarom (Universitas Islam Negeri Walisongo Semarang, 2021)
The purpose of this research is to describe the spirituality of rural Muslim communities through the routine activities of Jam’iyyah Nahdlatul Ulama from Ngemplak Simongan NU Sub-District. This research is a field research (qualitative) which elaborated phenomenology approach that uses observation, interviews, and documentation as a method of collecting data, which is also equipped with a library research. The research shows that the spirituality of the Muslim community and the Jam’iyyah NU, Ngemplak Simongan Village is also still very much carrying the spirit of local wisdom based on Islamic values to this day. They also still carry out Javanese religious rituals, such as routine recitation activities, tahlil, yasinan, diba’, istighāstah, manāqib, and ziyārah Walisongo, because they believe that basically all of these rituals are part of Islamic teachings and originated from Islamic teachings. Jam’iyyah NU Ngemplak Simongan can also be categorized as “Moderate Muslim” because they still uphold the values of locality in religion. Based on the results, it shows that Jam’iyyah NU, Ngemplak can be used as a miniature of NU moderation in suburban villages of Semarang City. Jam’iyyah NU, Ngemplak, which in fact is a sub-district in the metropolitan city of Semarang, Central Java, they often and routinely carry out Ahlussunnah wal Jama’ah An-Nahdliyyah (Aswaja NU) activities to maintain the spiritual spirit of rural Muslim communities.